THE COMMUNICATIVE APPROACH TO LANGUAGE TEACHING:THE KING IS DEAD! LONG LIVE THE KING! - Roberts, John T. (International Journal of English Studies, 2009)
The purpose of this paper is to argue that though the Communicative Approach to Languageteaching in its original sense has long been theoretically dead, it has for an almost equally long time at least potentially existed in a new form, and continues to thrive. By no means here for the first time is this sort of proposal made, but what remains to be done is to firmly pronounce the death of 'Communicative Approach to Language Teaching Mark II' and to formally welcome, if somewhat belatedly, that is to say, by at least 17 years, its successor: 'Communicative Approach to Language Teaching Mark II'. At the same time, the attempt to disambiguate 'Communicative Approach to Language Teaching' from 'Communicative Methodology' is made again, because students of Applied Linguistics often reveal a complete failure to grasp the difference, as well as failure to understand why the term 'Cornrnunicative Method' is meaningless. The story related here will be very familiar to some, but less so to others, which is why it is detailed. It is, of course, only one story, one interpretation, and there are others.